Characteristics and Antimicrobial Activities of Iron Oxide Nanoparticles Obtained via Mixed-Mode Chemical/Biogenic Synthesis Using Spent Hop (Humulus lupulus L.) Extracts - Jolanta Flieger; Sylwia Pasieczna-Patkowska; Natalia Żuk; Rafał Panek; Izabela Korona-Głowniak; Katarzyna Suśniak; Magdalena Pizoń; Wojciech Franus (MDPI AG, 2024)
Iron oxide nanoparticles (IONPs) have many practical applications, ranging from environmental protection to biomedicine. IONPs are being investigated due to their high potential for antimicrobial activity and lack of toxicity to humans. However, the biological activity of IONPs is not uniform and depends on the synthesis conditions, which affect the shape, size and surface modification. The aim of this work is to synthesise IONPs using a mixed method, i.e., chemical co-precipitation combined with biogenic surface modification, using extracts from spent hops (Humulus lupulus L.) obtained as waste product from supercritical carbon dioxide hop extraction. Different extracts (water, dimethyl sulfoxide (DMSO), 80% ethanol, acetone, water) were further evaluated for antioxidant activity based on the silver nanoparticle antioxidant capacity (SNPAC), total phenolic content (TPC) and total flavonoid content (TFC). The IONPs were characterised via UV-vis spectroscopy, scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS) and Fourier-transform infrared (FT-IR) spectroscopy. Spent hop extracts showed a high number of flavonoid compounds. The efficiency of the solvents used for the extraction can be classified as follows: DMSO > 80% ethanol > acetone > water. FT-IR/ATR spectra revealed the involvement of flavonoids such as xanthohumol and/or isoxanthohumol, bitter acids (i.e., humulones, lupulones) and proteins in the surface modification of the IONPs. SEM images showed a granular, spherical structure of the IONPs with diameters ranging from 81.16 to 142.5 nm. Surface modification with extracts generally weakened the activity of the IONPs against the tested Gram-positive and Gram-negative bacteria and yeasts by half. Only the modification of IONPs with DMSO extract improved their antibacterial properties against Gram-positive bacteria (Staphylococcus epidermidis, Staphylococcus aureus, Micrococcus luteus, Enterococcus faecalis, Bacillus cereus) from a MIC value of 2.5-10 mg/mL to 0.313-1.25 mg/mL.